Saúde mental da equipe de enfermagem em tempos de pandemia de covid-19 - Oliveira, Nahara de Castro (2023)
The world is facing a situation that has not yet been experienced with the COVID-19 pandemic, and the reality experienced by health professionals has led to the risk of being infected by the disease, which has had an impact on mental health, especially on the nursing team, which provides direct care to the user, affecting their well-being and ability to carry out their activities. At the beginning of the pandemic, there was panic in work environments and apprehension about the possibility of infection with the new coronavirus. The need to use Personal Protective Equipment (PPE), combined with the lack of these materials, in addition to the routine coping with situations of illness and death, generated psychological suffering in these workers. The chaotic situation generated by the pandemic brought changes to the daily lives of nursing professionals, generating a mix of feelings and sensations previously unknown to them and which affected their mental health. Given this situation, the objective of this research was to understand how the mental health of the nursing team is in times of the COVID-19 pandemic by surveying works that address this topic and identifying the aggravating factors present in the exercise of their role, in addition to pointing out coping strategies to improve and/or guarantee the mental health of these professionals. The methodology used was the Integrative Literature Review (RIL) of works written between 2020 and 2022 published in the Virtual Health Library (VHL). Of the 65 works analyzed, 11 were used for this research. To carry out the analysis of the articles, three categories were chosen to deepen the study: a) changes in the work environment as a result of the COVID-19 pandemic that affected the mental health ofnursing professionals; b) mental illness of nursing professionals manifested through various symptoms, with a prevalence of anxiety, depression and stress; c) lack of psychological support for nursing professionals. The research carried out concluded that there were changes in the mental health of these professionals related to changes made in the work environment due to the COVID-19 pandemic, as well as suggesting changes in the search for this health. Therefore, the use and maintenance of certain strategies to minimize mental health problems is recommended, as well as the implementation of other measures to improve the work environment with the aim of preserving/guaranteeing the mental health of these workers. The need for further investigation into the mental health of the nursing team related to the work environment was also verified, as well as the evaluation of the use of strategies used to promote the mental health of these professionals, in addition to the need to invest in improving quality of life at work, which is so necessary for health. Keywords: mental health; Nursing team; COVID-19.